2022
DOI: 10.1371/journal.pone.0272125
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breast milk feeding on early brain development in preterm infants in China: An observational study

Abstract: Background The prevailing consensus from large epidemiological studies is that breastfeeding is associated with improved IQ and cognitive functioning in later childhood and adolescence. Current research is exploring the association between breastfeeding and early brain development in preterm infants. Objective To explore the differences in brain gray matter between breastmilk-fed and formula-fed preterm infants using structural and functional magnetic resonance imaging. Methods A convenience sample of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…These results are replicated in the preterm literature, with human milk optimizing overall neurodevelopment [43,45,49,51,52,57]. In Niu et al, functional brain network architecture in preterm infants who were BF or FF were analyzed for the first-time using fMRI.…”
Section: Hmos' Effect On Preterm Infantsmentioning
confidence: 75%
“…These results are replicated in the preterm literature, with human milk optimizing overall neurodevelopment [43,45,49,51,52,57]. In Niu et al, functional brain network architecture in preterm infants who were BF or FF were analyzed for the first-time using fMRI.…”
Section: Hmos' Effect On Preterm Infantsmentioning
confidence: 75%
“…The results of this study show that the elicited dimension scores of the low breast milk feeding group were lower than those of the medium and high breast milk feeding groups, indicating that medium and high levels of breast milk feeding led to better development of EPIs’ responses to visual and auditory stimuli, defensive actions, trunk movement, and limb movement. A study by Zhang et al, showed that compared with infants fed with formula milk, those fed with breast milk had a larger volume of gray matter, especially in the bilateral frontal lobes, left caudate nucleus, and right temporal lobe [ 19 ]. The frontal lobe plays an important role in many processes, such as motor control, urination, cognition, attention, memory, language, and neuropsychiatric functions, while the temporal lobe is related to auditory, visual, memory, and language functions [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies on breastfeeding and its relationship with neurodevelopment focused on cognitive outcomes, whereby breastfeeding was generally associated with predicting greater academic achievements compared to formula feeding [ 224 , 225 ]. In preterm infants, breastmilk was also found to increase the rate of regional gray matter development when compared with formula-fed infants [ 226 ]. This observational study is the first to suggest that human milk exerts a direct and distinct effect on the brain structural development in humans.…”
Section: Maternal Factors Influencing Offspring Neurodevelopment and ...mentioning
confidence: 99%